m-Iodosylbenzoic acid as a convenient recyclable hypervalent iodine oxidant for the synthesis of α-iodo ketones by oxidative iodination of ketones - Yusubov M. S. Mekhman Suleiman-Ogly (Suleimanovich); Yusubova R. Ya. Roza Yavidovna; Funk T. V. Tatyana V.; Chi Ki-Whan; Kirschning A.; Zhdankin V. V. Viktor Vladimirovich (2010, 2010)
Title screen